Missed miscarriage and hyperprolactinemia. Is there a place for plant-derived medicines? - A.A. Olina (LCC «Medicine-Inform», 2020)
Missed miscarriage and hyperprolactinemia. Is there a place for plant-derived medicines? A.A. Olina D.O. Ott Research Institute of Obstetrics, Gynaecology and Reproduction, St. Petersburg, Russian Federation Aim: to analyze whether hyperprolactinemia contributes to missed miscarriage and to assess the efficacy of the treatment with plant-derived dopamine agonists. Patients and Methods: 375 women with anamnestic missed miscarriage before 14 weeks of pregnancy were enrolled. Women with the first and the only missed miscarriage (n=218) were included in group 1. Women with the first and subsequent pregnancies that resulted in intrauterine fetal death (n=157) were included in group 2. The levels of prolactin, thyroid-stimulating hormone (TSH), and thyroid peroxidase antibodies (TPO Abs) were measured. MRI with contrast was performed as needed. Cyclodynon® (1 tablet daily for 3 months) was prescribed for hyperprolactinemia. Results: elevated prolactin levels were revealed in 45 women (significant differences between group 1 and group 2 were demonstrated). All women with hyperprolactinemia underwent pituitary MRI with contrast. Pituitary microadenoma was identified in 16 w omen (group 1, n=5, 2.3%; group 2, n=11, 7.0%). In a total of 16 women, pituitary adenoma was identified for the first time. Gynecological examination has demonstrated that 20 women are infertile, i.e., 7 women in group 1 (3.2%) and 13 women in group 2 (8.3%). Elevated TSH was revealed in 23 women with missed miscarriage (6.1%), one in two woman (n=13) had hyperprolactinemia. Elevated TPO Abs were revealed in 59 women (15.7%), 17 out of 59 women (28.9%) had hyperprolactinemia, 17 out of 59 women (28.9%) had elevated THS, and 9 out of 59 women (15.3%) had hyperprolactinemia and elevated TSH. Conclusions: hyperprolactinemia was identified in every ten woman with anamnestic missed miscarriage. Significant differences between women with the only pregnancy loss and women with subsequent pregnancy loss were revealed. 35.6% of women with hyperprolactinemia were diagnosed with microadenoma. Treatment efficacy for both organic and functional hyperprolactinemia was 91.1%. Keywords: infertility, miscarriage, missed miscarriage, hyperprolactinemia, pituitary microadenoma, dopamine agonist. For citation: Olina A.A. Missed miscarriage and hyperprolactinemia. Is there a place for plant-derived medicines? Russian Journal of Woman and Child Health. 2020;3(2):64-69. DOI: 10.32364/2618-8430-2020-3-2-64-69.